Building Capability for Clinical Pharmacology Research in Sub‐Saharan Africa. Issue 5 (5th June 2017) - Gutierrez, MM; Pillai, G; Felix, S; Romero, F; Onyango, KO; Owusu‐Agyei, S; Asante, KP; Barnes, KI; Sinxadi, P; Allen, E; Abdulla, S; Masimirembwa, C; et al.
Abstract : A strong scientific rationale exists for conducting clinical pharmacology studies in target populations because local factors such as genetics, environment, comorbidities, and diet can affect variability in drug responses. However, clinical pharmacology studies are not widely conducted in sub‐Saharan Africa, in part due to limitations in technical expertise and infrastructure. Since 2012, a novel public‐private partnership model involving research institutions and a pharmaceutical company has been applied to developing increased capability for clinical pharmacology research in multiple African countries.